2009
DOI: 10.1002/jobm.200800070
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and phenotypic diversity of Anabaena isolates from diverse rice agro‐ecologies of India

Abstract: The genus Anabaena is one of the commonly observed genera in the rice fields in South-east Asia. Diversity analyses of a set of 70 Anabaena strains (including 67 strains isolated from diverse rice agro ecologies of India, and three International Reference/Type strains), was carried out using morphological and molecular datasets. The pattern of growth in liquid and solid medium and microscopic observations revealed tremendous diversity in the Anabaena germplasm analysed. The species wise distribution in differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Isolates belonging to two Anabaena species (Anabaena fertilissima RPAN1 and Anabaena sphaerica RPAN12) that have different antifungal activities (31) were used in this investigation; these isolates are part of the germplasm of Anabaena isolates from diverse agro-ecological areas of India (25). The phytopathogenic fungus F. oxysporum, which causes diseases of various crops (tomato, chili, pepper, brinzal, red gram, ginger, linseed, etc.…”
Section: Methodsmentioning
confidence: 99%
“…Isolates belonging to two Anabaena species (Anabaena fertilissima RPAN1 and Anabaena sphaerica RPAN12) that have different antifungal activities (31) were used in this investigation; these isolates are part of the germplasm of Anabaena isolates from diverse agro-ecological areas of India (25). The phytopathogenic fungus F. oxysporum, which causes diseases of various crops (tomato, chili, pepper, brinzal, red gram, ginger, linseed, etc.…”
Section: Methodsmentioning
confidence: 99%
“…Smith et al (1998) suggested the utility of highly iterated palindromic sequences (HIP), based assay in distinguishing cyanobacterial species and strains. Earlier studies (Prasanna et al 2006;Sood et al 2008;Nayak et al 2009) also revealed that such molecular polymorphisms can aid in understanding genetic relationships and differentiation of the Anabaena/ Nostoc strains.…”
Section: Discussionmentioning
confidence: 92%
“…(Singh and Bisoyi 1989;Prasanna and Nayak 2007;Nayak et al 2001Nayak et al , 2004Nayak et al , 2009). Earlier, Kaushik and Prasanna (1995) had demonstrated the existence of competition among the strains used in cyanobacterial biofertilizer consortia with dominance of one or two strains (generally Anabaena or Nostoc sp.)…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The chitosanase homologue responsible for fungicidal activity had been earlier identified in this strain (Prasanna et al 2010a). This strain has been previously identified both morphologically (Nayak et al 2009) as well as on the basis of 16S rDNA (Accession number GQ466518, GQ466546, GQ466574). Firstly, the genomic library for RPAN8 was constructed which generated 2000 clones each having 2-5 kb fragment size.…”
Section: Discussionmentioning
confidence: 97%